The Use of Biotechnological Drugs in Pediatrics on the Example of Monoclonal Antibodies: Clinical Pharmacology View - Alexey S. Kolbin; Liudmila I. Yemelyanova (Union of pediatricians of Russia, 2021)
The article reviews monoclonal antibodies, its structure, classifications, pharmacodynamics, pharmacokinetics, and adverse effects. There are examples for each section. Approaches to the research and criteria for drug selection in paediatrics are discussed in detail: the role of clinical trials, extrapolation and pharmacometrics. It has been shown that the differences in the pharmacokinetics of monoclonal antibodies between adults and children present due to the age-related characteristics of various physiological processes. The authors analyse such parameters as absorption, bioavailability, distribution, and elimination. The role of monoclonal antibodies immunogenicity in the structure of adverse effects in children is fully presented. Pharmacometrics is reviewed in the form of modelling and simulation in monoclonal antibodies dosing in paediatrics. It is important to consider the growth and development as "moving targets" in pediatrics regardless the principle of monoclonal antibodies dosage in children. The conclusions were made, and the guidelines were prepared based on the article results.